PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN BUDAYA MAPALUS PADA MASA PANDEMI COVID-19 DI DESA PICUAN SATU KECAMATAN MOTOLING TIMUR KABUPATEN MINAHASA SELATAN - Sumangkut, Wendi; Mumu, Rudy; Goni, Shirley Y. V. I. (Universitas Sam Ratulangi, 2021)
This research aims to determine the participation of the community in the development of Mapalus culture during the Covid 19 Pandemic in Desa Picuan Satu Kecamatan Motoling Timur, Kabupaten Minahasa Selatan. The research uses descriptive design qualitative analysis. Data collection techniques used are observation, interview, and documentation. To see how community participation in Mapalus cultural development during the covid 19 pandemic in Desa Picuan Satu. Researchers use 4 indicators, namely: family, consensus deliberation, cooperation, unity and unity. Based on the results of the research shows that the culture of